2007
DOI: 10.1021/jf070529g
|View full text |Cite
|
Sign up to set email alerts
|

Phycobiliprotein C-Phycocyanin from Spirulina platensis Is Powerfully Responsible for Reducing Oxidative Stress and NADPH Oxidase Expression Induced by an Atherogenic Diet in Hamsters

Abstract: The effects of spirulina and its chromophore phycocyanin, both without bound Se or selenium-enriched, were studied on plasma cholesterol, early atherosclerosis, cardiac production of superoxide anions, and NAD(P)H oxidase expression in hamsters. Forty hamsters were divided into 5 groups of 8 and fed an atherogenic diet for 12 weeks. They received by gavage either 7.14 mL/(kg day) phycocyanin (PC), Se-rich phycocyanin (SePC), spirulina (SP) or Se-rich spirulina (SeSP) in water, or water as control. SeSP and SeP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 34 publications
7
117
0
2
Order By: Relevance
“…57 Although the clinical utility of ample intakes of spirulina has so far received little research attention, in numerous rodent studies orally administered spirulina or phycocyanin has shown potent anti-inflammatory, cytoprotective, and anti-atherogenic activities; these effects are most likely attributable to down-regulation of NADPH oxidase activity. 51,52,58,59 A consideration of the central role of NADPH oxidase over-activity in a range of disorders suggests that ample intakes of spirulina may have preventive and therapeutic potential with respect to many vascular diseases (including atherogenesis, hypertension, and congestive heart failure), cancers, complications of diabetes, and a range of neurodegenerative, fibrotic, or inflammatory disorders. 51,52 It should be emphasized that measures which inhibit NADPH oxidase activity could be expected to have a much more profound health impact than antioxidant vitamins or phytochemicals that act merely as oxidant scavengers -the latter, while helping to preserve the structural integrity of membrane lipids or proteins, have little influence on the signal-modulatory activity of hydrogen peroxide, or on the nitric oxide-quenching activity of superoxide.…”
Section: Spirulina Has Profound Antioxidant Potentialmentioning
confidence: 99%
“…57 Although the clinical utility of ample intakes of spirulina has so far received little research attention, in numerous rodent studies orally administered spirulina or phycocyanin has shown potent anti-inflammatory, cytoprotective, and anti-atherogenic activities; these effects are most likely attributable to down-regulation of NADPH oxidase activity. 51,52,58,59 A consideration of the central role of NADPH oxidase over-activity in a range of disorders suggests that ample intakes of spirulina may have preventive and therapeutic potential with respect to many vascular diseases (including atherogenesis, hypertension, and congestive heart failure), cancers, complications of diabetes, and a range of neurodegenerative, fibrotic, or inflammatory disorders. 51,52 It should be emphasized that measures which inhibit NADPH oxidase activity could be expected to have a much more profound health impact than antioxidant vitamins or phytochemicals that act merely as oxidant scavengers -the latter, while helping to preserve the structural integrity of membrane lipids or proteins, have little influence on the signal-modulatory activity of hydrogen peroxide, or on the nitric oxide-quenching activity of superoxide.…”
Section: Spirulina Has Profound Antioxidant Potentialmentioning
confidence: 99%
“…S. platensis has been approved as a health food by the World Health Organization (WHO) and it will become one of the most alternative treatments in the 21 st century [25,26] . Researchers have reported the effects of S. platensis on blood protein and lipid content [23,27,28] , and their antioxidant, antiviral and immunmodulator activities [24,29,30] in animals. According to some researchers, S. platensis and its extract may decrease the blood lipid values.…”
Section: Introductionmentioning
confidence: 99%
“…According to some researchers, S. platensis and its extract may decrease the blood lipid values. Especially, phycocyanin and polyunsaturated fatty acids in S. platensis may play an important role in its hypocholesterolemic effect [28,29,31] . Nagaoka et al [23] reported that cholesterol is lowered by inhibition of the cholesterol absorption from jejunum and bile acid resorption from ileum with phycocyanin in S. platensis.…”
Section: Introductionmentioning
confidence: 99%
“…potent peroxy radical scavenger in vitro and in vivo (Bhat and Madyastha, 2000). The chromophore phycocyanobilin of phycocyanin is reduced in mammals to phycocyanorubin (Terry et al, 1993), which can inhibit formation of superoxide radicals by NADPH oxidase complex (McCarty, 2007;Riss et al, 2007). These findings imply that phycoerythrobilin as well as phycocyanobilin can be metabolized to function in mammalian cells.…”
Section: Resultsmentioning
confidence: 99%